Variations of perceived load and well-being between normal and congested weeks in elite case study handball team - Clemente, F. M.; Oliveira, H.; Vaz, T.; Carriço, S.; Calvete, F.; Mendes, B. (Research in Sports Medicine, 2019)
The aim of this study was two-fold: (i) to analyze the variations in internal load and well-being in professional handball players between normal and congested weeks and (ii) to analyze the variations between training days within weeks. Twenty male players (26.5 ± 4.9 yo) were monitored during a full season. MD-1 (match day -1) revealed larger decreases in muscle soreness (-17.3%, [-26.6;-6.9]) and fatigue (-16.6%, [-24.8;-7.4]) in congested weeks. Regarding MD-2, larger decreases in DOMS (-19.9%, [-30.5;-7.6]), fatigue (-19.7%, [-30.0;-7.9] and the Hooper index (-16.7%, [-25.6;-6.7]) were found in congested weeks. The results of this study reveal that larger variations between normal and congested weeks occurred in MD-2 and MD-3, with greater values of load and lower levels of well-being occurring in normal weeks. Within-weeks changes revealed greater loads occurring on MD-3 and MD-2 in comparison to MD-1; in the opposite way, greater values of muscle soreness and fatigue occurred on MD-1.